Deriva Litorânea ao Longo da Costa do Cacau, Bahia: Repercussões na Geomorfologia Costeira - DO NASCIMENTO, LUCAS; BITTENCOURT, ABÍLIO; SANTOS, ADEYLAN NASCIMENTO; LANDIM DOMINGUEZ, JOSÉ MARIA (Pesquisas em Geociências, 2007)
<!– .p text-align: justify; –> In this study the patterns of sediment dispersion along part of the southern coast of Bahia, known as the Cacao Coast, were defined, starting with a numerical modeling on wave refraction diagrams. These patterns are able to reproduce net longshore drift direction of sediments in sections where there are geomorphic evidences of the longshore drift direction, and also reasonably explain the different coastal sections under deposition and erosion or little/no deposition, identified by walking the entire extension of the area under study. In a general way, the Cacao Coast may be divided into two sectors with well-defined characteristics: a) the northern half, with a predominance of sections under erosion or little/no deposition, and b) the southern half, with a predominance of sections under deposition.